Analisis peran guru dalam penanaman sikap sosial siswa pada proses pembelajaran ips tatap muka terbatas kelas v sekolah dasar - Nida Azizah; Siti Istiyati; Siti Kamsiyati (Universitas Sebelas Maret, 2023)
Abstract. This study aims to describe the role of teachers in instilling social attitudes of grade V students through the social studies learning process Face-to-face is limited. This research is a descriptive qualitative research. Subject This study included five student respondents and one grade V B elementary school teacher Mangkubumen Kidul No. 16 Surakarta. Data collection is carried out by observation, interview, and questionnaire techniques. Test the validity of data in This study used triangulation techniques and time. Data analysis using interactive analysis models by Miles and Huberman. The results of this study show that teachers instill social attitudes in social studies learning through the application of learning strategies in the form of routine activities, modeling activities, and spontaneous activities. Each component of RPP are linked to instilling social attitudes at the beginning, core, and end of learning. Based on data analysis related to the form of instilling social attitudes, the average grade V B student has shown a form of honest social attitude, courtesy, discipline, tolerance, and please help. It can be concluded that the teacher plays an important role in instilling students' social attitudes in the process Face-to-face social studies learning is limited to class V B.Kata kunci: Instillation of social attitudes, Social Sciences, limited face-to-face learning, primary school, elementary school